Beak deviations in the skull of Franciscana dolphins Pontoporia blainvillei from Argentina - Denuncio, Pablo Ezequiel (2016)
The Franciscana dolphin Pontoporia blainvillei is characterized by a long rostrum, a feature that is shared with the families formerly classified as river dolphins (Pontoporiidae, Platanistidae, Iniidae, Lipotidae). Although there are occasional reports on the existence of beak deformations, very little published information exists describing this process. The object of the present study was to describe and quantify the beak anomalies of Franciscana dolphins from the coastal waters of Argentina. Of 239 skulls analyzed 12% showed beak deviations (BD), affecting the premaxillary-maxillary and dentary bones to different extents. The occurrence of BD in the dentary bone represented 58%, whereas premaxillary-maxillary BDs were observed in 14% ofthe studied specimens, while the complete rostrum (dentary, premaxillary and maxillary) was affected in 28% of the skulls. Dorsoventral axis BD was more frequent than lateral BD (48 and 38%, respectively), and double BD was only observed in the dentary bone. Most of the BD observed in this study could be classified as mild/moderate, and we assume that it did not affect the feeding activities of individuals; however, 2 specimens (<1%) showed a severe and complex curvature that probably did affect them. The cause of these anomalies (natural or anthropogenic origins) is unknown but may be related to important parasite loads, heavy metal and organic contaminants and plastic ingestion that could affect the coastal dolphin in different ways. A more detailed and thorough study of these cranial anomalies is necessary.